Learning Styles, Self-Regulation and Reading Achievement: Evidence From Indonesia (Conference on English Language Teaching, 2023)
The purpose driving the study is to investigate and explain the relationship between students’ learning styles, self-regulation and reading achievement of Islamic Junior High Schools. Eighty students purposively chosen participated in the study. Sixty five are female students, and fifteen were male students. Index of Learning Style (ILS), designed by Felder-Silverman, was employed to elicit data on learning style preferences. It has four bipolar dimensions: active-reflective, sensing-intuitive, verbal-visual, and sequential-global. To measure students’ self-regulation consisting of 32 questions was used, while reading achievement was measured through reading test. The data were analysed through Eta correlation test and Product moment. The finding reveals that active and sensing learning styles gained the highest total number of students, each with 27 students. The lowest is sequential with only 2 students. Furthermore, of eighty respondents, there are three in very good category of self-regulation ability, while the rest is in good self-regulation. None is in either poor or fair. Statistically, the findings reveal that there is a significant relationship between learning styles and reading achievement among Islamic Junior High School Students; there is no significant correlation between self-regulation and reading achievement; and there is no significant correlation between self-regulation and reading achievement.